Exploring the use of content and language integrated learning for online learning in Chemistry major - Reski Kartini Addas; Muliati Muliati; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2022)
The world of education is mainly presented in the form of bilingual learning, such as in universities. Furthermore, some departments prepare majors with international class programs. This research focuses on analyzing the chemistry students’ perceptions and the practice of the subject on the use of content language Integrated learning. The samples were seven students who learned and one lecturer who taught chemistry major for an international class in Universitas Negeri Makassar. The researcher took them by using purposive sampling. The research instruments were interview protocol for semi-structured interviews, observation checklist, and documentation. Based on data analysis by using thematic analysis, it gathered results; first, from the chemistry students’ perceptions towards the use of the content and language integrated learning, the researcher found several themes for each aspect: perception of content was content material, language use, medium of instruction, and teaching style; perception of cognitive were classroom condition, critical thinking, problem-solving, and learning motivation; perception of communication was learning difficulties, English use, learning style, and reason for learning style; perception of culture were code-mixing use and learning-interaction. The perceptions are also mainly influenced by factors of expectations and experiences. Second, from the learning process of the Analytic Chemistry subject that practiced the CLIL, the researcher found that in all of the stages in the learning process: pre-activity, main-activity, and post-activity. English and Indonesian also play a role in this learning process. The lecturer actively combines these two languages to deliver the material, and the students respond to the lecturer. Therefore, it is recommended that in using and developing content and language integrated learning, the university may consider the perceptions of these students and difficulties for lecturers and students in the learning process, especially in bilingual online classes at the university level.